Chronic CRH depletion from GABAergic, long-range projection neurons in the extended amygdala reduces dopamine release and increases anxiety - Dedic, Nina; Kuehne, Claudia; Jakovcevski, Mira; Hartmann, Jakob; Genewsky, Andreas J.; Gomes, Karina S. [UNESP]; Anderzhanova, Elmira; Poehlmann, Max L.; Chang, Simon; Kolarz, Adam; Vogl, Annette M.; Dine, Julien; et al. (Nature Publishing Group, 2018)
The interplay between corticotropin-releasing hormone (CRH) and the dopaminergic system has predominantly been studied in addiction and reward, while CRH-dopamine interactions in anxiety are scarcely understood. We describe a new population of CRH-expressing, GABAergic, long-range-projecting neurons in the extended amygdala that innervate the ventral tegmental area and alter anxiety following chronic CRH depletion. These neurons are part of a distinct CRH circuit that acts anxiolytically by positively modulating dopamine release.